PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN SUSU BEAR BRAND MELALUI KEPUASAN KONSUMEN SEBAGA VARIABEL INTERVENING PADA MAHASISWA FEB UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Nurhasana, Tutut; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
PT Nestlé Indonesia is a multinational corporation that manufactures a wide range of packaged beverages, including Bear Brand sterilized milk. Data from the 2024 Top Brand Index (TBI) indicate that Bear Brand is one of the highest-ranking ready-to-drink milk products, surpassing many of its competitors. Accordingly, this study focuses on Bear Brand milk consumers within the students of the Faculty of Economics and Business at Universitas Abdurachman Saleh Situbondo. The population of this study comprises all active students of the Faculty of Economics and Business at Universitas Abdurachman Saleh Situbondo. The sampling technique employed is purposive sampling. Data analysis and hypothesis testing are conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of hypothesis testing using the SmartPLS 3.0 application indicate that both price and product quality have a positive but insignificant effect on consumer satisfaction, while brand image has a positive and significant effect on consumer satisfaction. Price demonstrates a positive but insignificant effect on consumer loyalty. In contrast, product quality has a positive and significant effect on consumer loyalty, and brand image has a positive but insignificant effect on consumer loyalty. Furthermore, consumer satisfaction has a proven positive and significant effect on consumer loyalty. Indirectly, both price and product quality have a positive but insignificant effect on consumer loyalty through consumer satisfaction. On the other hand, brand image has a positive and significant indirect effect on consumer loyalty through consumer satisfaction.